UPAYA GURU NGAJI DALAM MENGHIDUPKAN TRADISI KHATAM AL-QUR’AN DI KALANGAN GENERASI ALPHA DI DESA SUNGAI JAMBAT KECAMATAN SADU KABUPATEN TANJUNG JABUNG TIMUR PROVINSI JAMBI - Ayuni, Putri; M. Yahuda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the declining practice of the Khatam Al-Qur'an tradition, especially among the younger generation. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The research subjects consisted of Qur'an teachers, students from Generation Alpha, and parents in Sungai Jambat Village. Data analysis was conducted using descriptive qualitative techniques through the interpretation of field data to answer the research questions. The results of the study show that Qur'an teachers have made various efforts to revive the Khatam Al-Qur'an tradition, including active mentoring, instilling discipline, providing consistent motivation, and involving parental support. Supporting factors include the patient and careful guidance of the teachers, adequate facilities, parental involvement, and the students’ internal motivation. Meanwhile, the inhibiting factors include excessive use of mobile phones, limited ability to read the Qur'an among some students, students who stop before completing their recitation, and students’ responsibilities in helping their parents. Although there are no students who have completed reciting the full 30 juz yet, this research found several forms of success, such as improved fluency and quality in reading the Qur'an, increased motivation to continue reading, improved discipline and attendance, the formation of reading habits outside learning hours, and increased religious awareness in daily life. This study concludes that Qur'an teachers play a very important role in reviving the Khatam Al-Qur'an tradition, although support and cooperation from parents, the community, and the government are still needed.